Level of Satisfaction on Sports Facilities and Infrastructure among Students of Sport-Specific Class in A Senior High School - Asmaa Abusamra; Slamet Lestari; Dyssa Arfiesta Valentin Fajri (Jurnal Manajemen Pendidikan : Jurnal Ilmiah Administrasi, Manajemen dan Kepemimpinan Pendidikan, 2020)
This study aims to investigate the students’ levels of satisfaction on sport-specific class facilities and infrastructure in SMA N 4 Yogyakarta. This is a quantitative descriptive study that involves as many as 64 students of the tenth and eleventh grades of sport-specific classes. The data of this study were collected through surveys and observations before being analyzed using the descriptive statistics method. The results of this study show that the student level of satisfaction on sports facilities and infrastructure in SMA N 4 Yogyakarta is in the "moderate" category. Furthermore, seen from the categories of the service quality determinants, the aspect of reliability is in the “high” category while the tangibility is in the “very low” category.